1999
DOI: 10.1007/s11626-999-0060-2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of three-dimensional assembly of human liver cells by simulated microgravity

Abstract: The establishment of long-term cultures of functional primary human liver cells (PHLC) is formidable. Developed at NASA, the Rotary Cell Culture System (RCCS) allows the creation of the unique microgravity environment of low shear force, high-mass transfer, and 3-dimensional cell culture of dissimilar cell types. The aim of our study was to establish long-term hepatocyte cultures in simulated microgravity. PHLC were harvested from human livers by collagenase perfusion and were cultured in RCCS. PHLC aggregates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(65 citation statements)
references
References 19 publications
(25 reference statements)
3
62
0
Order By: Relevance
“…Again, such modalities are at an experimental stage, and their applicability remains to be confirmed. [67][68][69][70][71][72] …”
Section: Novel Culture Modalitiesmentioning
confidence: 99%
“…Again, such modalities are at an experimental stage, and their applicability remains to be confirmed. [67][68][69][70][71][72] …”
Section: Novel Culture Modalitiesmentioning
confidence: 99%
“…The rat pheochromocytoma (PC12) cells cultured in the RWV showed formation of large aggregates exhibiting neuroendocrine differentiation and altered cellular signaling mechanisms (Lelkes et al, 1998). Human hepatocytes formed three-dimensional assemblies when exposed to simulated micro-g (Khaoustov et al, 1999). Cultures of PC12 and SH-SY5Y cells in the simulated micro-g resulted in high cell viability and cell aggregation (Wang and Good, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…can be achieved by culturing primary tissues or established cell lines within extracellular matrix gels, synthetic scaffolds, rotary cell culture systems, or on low/non-adherent culture plastics; [6][7][8][9][10][11] these 3D cell culture techniques all aim to restore the 3D architecture that characterizes normal tissues and solid tumors alike. Studies have shown that gene expression profiles of 3D-cultured cells are dramatically different to monolayer cultures and more closely resemble the profiles of the tissues of origin than their 2D counterparts.…”
mentioning
confidence: 99%